Indirect effects of the early childhood Family Check-Up on adolescent suicide risk: The mediating role of inhibitory control. (December 2019) - Connell, Arin M.; Shaw, Daniel; Wilson, Melvin; Danzo, Sarah; Weaver-Krug, Chelsea; Lemery-Chalfant, Kathryn; Dishion, Thomas J.
Abstract: This study investigates suicide risk in late childhood and early adolescence in relation to a family-centered intervention, the Family Check-Up, for problem behavior delivered in early childhood. At age 2, 731 low-income families receiving nutritional services from Women, Infants, and Children programs were randomized to the Family Check-Up intervention or to a control group. Trend-level main effects were observed on endorsement of suicide risk by parents or teachers from ages 7.5 to 14, with higher rates of suicide risk endorsement in youth in the control versus intervention condition. A significant indirect effect of intervention was also observed, with treatment-related improvements in inhibitory control across childhood predicting reductions in suicide-related risk both at age 10.5, assessed via diagnostic interviews with parents and youth, and at age 14, assessed via parent and teacher reports. Results add to the emerging body of work demonstrating long-term reductions in suicide risk related to family-focused preventive interventions, and highlight improvements in youth self-regulatory skills as an important mechanism of such reductions in risk.